Nursing students' understanding of the Fundamentals of Care: A cross‐sectional study in five countries. Issue 11 (17th April 2018) - Jangland, Eva; Mirza, Noeman; Conroy, Tiffany; Merriman, Clair; Suzui, Emiko; Nishimura, Akiko; Ewens, Ann
Abstract : Aim and objective: To explore the accuracy with which nursing students can identify the fundamentals of care. Background: A challenge facing nursing is ensuring the fundamentals of care are provided with compassion and in a timely manner. How students perceive the importance of the fundamentals of care may be influenced by the content and delivery of their nursing curriculum. As the fundamentals of care play a vital role in ensuring patient safety and quality care, it is important to examine how nursing students identify these care needs. Design: Cross‐sectional descriptive design. Methods: A total of 398 nursing students (pre‐ and postregistration) from universities in Sweden, England, Japan, Canada and Australia participated. The Fundamentals of Care Framework guided this study. A questionnaire containing three care scenarios was developed and validated. Study participants identified the fundamentals of care for each of the scenarios. All responses were rated and analysed using ANOVA. Results: The data illustrate certain fundamentals of care were identified more frequently, including communication and education; comfort and elimination, whilst respecting choice, privacy and dignity were less frequently identified. The ability to identify all the correct care needs was low overall across the pre‐ and postregistration nursing programmes in the five universities. Significant differences in the number of correctly identified care needs between some of the groups were identified. Conclusions: Nursing students are not correctly identifying all a patient's fundamental care needs when presented with different care scenarios. Students more frequently identifying physical care needs and less frequently psychosocial and relational needs. The findings suggest educators may need to emphasise and integrate all three dimensions. Relevance to clinical practice: To promote students' ability to identify the integrated nature of the fundamentals of care, practising clinicians and nurse educators need to role model and incorporate all the fundamental care needs for their patients.